Pengoptimalan Efisiensi Panel Surya: Integrasi Pelacakan dan Reflektor Sumbu Ganda Tenaga Surya - Alvin Rinaldi Wiharja; Levin Halim; Faisal Wahab (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
Solar panels have relatively low efficiency, but their performance can be enhanced by a tracking system directing the panels perpendicular to the light source and adding reflectors to capture more sunlight. The dual-axis solar tracking method, using two linear actuators and optimized by fuzzy logic, efficiently positions solar panels for maximum sunlight exposure. This research aimed to improve the overall efficiency of solar panels by integrating reflectors with a dual-axis solar tracking system optimized by fuzzy logic. Specifically, this research tested various reflectors to determine the most significant efficiency improvement. This research consisted of two tests: a tracking test and a reflector test using a halogen lamp. The tracking test was conducted by positioning the light in four different positions. The light sensor data were obtained before and after the solar tracking, indicating that the tracking was successful. All these tests were conducted with the light source radiation of 1,168 W/m2. This research concluded that the tracking system effectively positioned the solar panels toward the light source, with the tracking time ranging from 12 to 16 s, depending on the position. Aluminum foil is the most cost-effective reflector, priced at IDR5,341 per 1% increase in efficiency, compared to mirrors at IDR20,204 per 1% and reflective tape at IDR48,034 per 1%. In conclusion, the integration of aluminum foil reflectors and a dual-axis solar tracking system, optimized by fuzzy logic, significantly improves the efficiency of solar panels, which is both cost-effective and efficient.